Arming Asia technonationalism and its impact on local defense industries - Bitzinger, Richard (Routledge security in Asia, 2017)
Examines the phenomenon of attempted self-reliance in arms production within Asia, and assesses the extent of success in balancing this independence with the growing requirements of next-generation weapons systems. He analyzes China, India, Japan, South Korea, and Southeast Asia. The overarching question in the book is whether self-reliance is a strategically viable solution for development and manufacturing of arms. Given the ever-changing dynamics and increasing demand for sophisticated next-generation weaponry, will these countries be able to individually sustain their domestic defense industries and constantly update their technologies? This is the first book to analyze arms production from a regional perspective